Otomasi ULFJ Margonda Raya Sebagaimana Diatur Melalui Permen PUPR Tentang ULFJ dengan Menggunakan Algoritma Aplikasi Ms. Excel - Sumabrata, Jachrizal; Parlambang, Satria Adipradana; Adwitiya, R Ivan (Universitas Jember, 2023)
One of the leading causes of death on earth is traffic accidents. Traffic accidents occur for many reasons. One reason is the condition of the road itself. Depok is a sub-urban area of Greater Jakarta that has the Margonda Highway as one of its main roads. That highway has become strategic as a